OPTIMALISASI PERENCANAAN BERBASIS DATA DI SD NEGERI 4 MUARA PINANG - Mulyono, Dodik (FIP UNIRA MALANG, 2025)
Data-driven planning is a crucial element in achieving effective, accountable, and quality-oriented school management. However, many primary schools, including SD Negeri 4 Muara Pinang, have yet to fully utilize data in developing their annual work plans. This community service activity aimed to enhance the understanding and skills of school stakeholders in reading, analyzing, and integrating data into the planning process. The methods involved initial needs assessment, workshops and training sessions, planning assistance, and evaluation. The results indicated a significant improvement in participants’ understanding, with the average pre-test score rising from 48.3% to 83.6% in the post-test. Furthermore, there was a clear shift in the planning approach, which now refers to data sourced from the Education Report Card (Rapor Pendidikan) and E-RKAS. This activity not only improved the quality of school planning but also fostered a culture of data-driven decision-making. It is recommended that similar initiatives be replicated in other schools with contextual adjustments and supported by continuous capacity-building programs to ensure sustainability.